Towards Indicators for Assessing Land-Use Change in Planning: Case Study of the Peri-Urban Zone of Thessaloniki - Nadia Bessa (European Regional Science Association (ERSA), 2006)
Expanding urban areas face growing land use conflicts particularly in the peri-urban zone, which is defined as a zone outside the city, occupied both by 'classical' rural land uses, and construction of road infrastructure and commercial shopping centers, which result as rapid changes. These changes of the peri-urban zone lead to complex patterns of land uses as evidenced in terms of the intensity and structure. To the extent that modern societies need to understand such patterns in order to formulate appropriate guidance policies, it is interesting to develop a relevant framework of analysis. It is necessary to assess land-use change in order to assist urban planning and related decision-making. The proposed approach explores an analytical framework combining GIS and a system of PSI (pressure-state-impact) indicators aimed at the analysis of urban growth and land use change in the peri-urban zone of Thessaloniki. Thessaloniki is the second largest city of Greece which is located in the Northern part of the country and has approximately one million inhabitants.
Keywords: 330